Manganese-chlorine co-doped carbon nitride and photocatalytic hydrophobic self-cleaning coating based on manganese-chlorine co-doped carbon nitride
Through the preparation of manganese chlorine co-doped carbon nitride and its combination with materials such as epoxy resin, the problems of limited light absorption capacity of graphite phase carbon nitride and poor durability of superhydrophobic coating are solved, and high-efficiency photocatalysis and good hydrophobic properties are achieved.
Patent Information
- Application Number
- CN202411830936.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-14
AI Technical Summary
The existing graphite phase carbon nitride has a small specific surface area, a wide band gap, limited light absorption capacity, and poor superhydrophobic durability of superhydrophobic-photocatalytic synergistic self-cleaning coatings.
By the preparation method of manganese chlorine co-doped carbon nitride, manganese chlorine co-doped carbon nitride with a petal-like structure is obtained by uniform grinding and heat treatment of melamine, ammonium chloride and manganese chloride, and combined with epoxy resin, polydimethylsiloxane and 3-aminopropyltriethoxysilane to prepare a photocatalytic hydrophobic synergistic self-cleaning coating.
The specific surface area and pore structure of carbon nitride are improved, the efficiency and hydrophobic properties of photocatalytic reactions are enhanced, and the photocatalytic activity and durability of the coating are significantly improved.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalysis and relates to a manganese-chlorine co-doped carbon nitride and a photocatalytic hydrophobic self-cleaning coating based thereon. Background Art
[0002] Particulate matter and other components in the atmosphere, such as volatile organic compounds and nitrogen oxide gases, are widely deposited on the surface of buildings, affecting the life of the walls. Therefore, there is an urgent need to construct functional coatings with the ability to remove pollutants. Inspired by natural photosynthesis, photocatalysts with catalytic oxidation ability are combined with polymers to prepare photocatalytic coatings. Due to the advantages of simple structure, strong usability and low cost, the coating has been successfully applied to the degradation of dyes, volatile organic compounds (VOCs), bacteria, fungi and nitrogen oxide gases (NO).
[0003] Graphitic carbon nitride (g-C3N4) is widely used in the field of photocatalysis due to its advantages such as low cost and simple preparation process. However, g-C3N4 has the disadvantages of small specific surface area, wide band gap and limited light absorption capacity, which restricts its application in the field of photocatalytic degradation of pollutants. Therefore, many modification methods have been developed to optimize its performance. The main modification methods of g-C3N4 include morphology control, element doping, precious metal surface deposition, semiconductor composite modification and defect structure design. Its redox potential can be adjusted by anion and cation doping or co-doping. However, the modified g-C3N4 still has the problem of low utilization rate of visible light, which affects its use.
[0004] In addition, for the construction of coatings, epoxy resins are used in photocatalytic coatings due to their low toxicity, strong adhesion, excellent dispersion characteristics and bonding strength. However, due to its poor durability of superhydrophobicity, the widespread application of superhydrophobic-photocatalytic synergistic self-cleaning coatings is limited. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a manganese-chlorine co-doped carbon nitride and a photocatalytic hydrophobic self-cleaning coating based thereon, thereby solving the technical problems in the prior art of small specific surface area, wide band gap and limited light absorption capacity of graphite phase carbon nitride. At the same time, the present invention also solves the technical problem of poor super-hydrophobic durability of existing super-hydrophobic-photocatalytic synergistic self-cleaning coatings.
[0006] The present invention is achieved through the following technical solutions: A method for preparing manganese-chlorine co-doped carbon nitride comprises the following steps: S1: uniformly grinding melamine, ammonium chloride and manganese chloride to obtain a mixed powder; S2: heat-treating the powder in an air atmosphere to obtain the manganese-chlorine co-doped carbon nitride.
[0007] Preferably, the mass ratio of ammonium chloride to melamine is (0.8-1.2):1.
[0008] Preferably, the mass ratio of manganese chloride to melamine is (0.01-0.2):4.
[0009] Preferably, the grinding time is 30 to 50 min.
[0010] Preferably, during the grinding process, the mixture is ground to 400-600 mesh.
[0011] Preferably, the heat treatment temperature is 500-600° C., the heating rate is 4-5° C. / min, and the calcination time is 1.5-2.5 h.
[0012] A manganese-chlorine co-doped carbon nitride is prepared by the above method.
[0013] A photocatalytic hydrophobic synergistic self-cleaning coating comprises the above-mentioned manganese-chlorine co-doped carbon nitride.
[0014] The above-mentioned method for preparing a photocatalytic hydrophobic synergistic self-cleaning coating comprises mixing epoxy resin, polydimethylsiloxane, 3-aminopropyltriethoxysilane and a catalyst, stirring for reaction, adding a curing agent to obtain a water-based epoxy resin emulsion; and then adding the manganese-chlorine co-doped carbon nitride to obtain the photocatalytic hydrophobic synergistic self-cleaning coating.
[0015] A photocatalytic hydrophobic synergistic self-cleaning coating comprises a bottom layer and a surface layer, wherein the bottom layer is obtained by drying a water-based epoxy resin emulsion, and the surface layer is obtained by drying the above-mentioned photocatalytic hydrophobic synergistic self-cleaning coating.
[0016] Compared with the prior art, the present invention has the following beneficial technical effects: The invention discloses a preparation method of manganese-chlorine co-doped carbon nitride. According to the method, melamine, ammonium chloride and manganese chloride are uniformly ground to obtain a mixed powder, and then the mixed powder is heat-treated to effectively obtain the manganese-chlorine co-doped carbon nitride. Since the atomic radius of manganese chlorine is relatively large, the interlayer spacing of the carbon nitride is effectively increased. Due to the increase in the interlayer spacing, the separation of carriers is facilitated, and a larger space is provided for photogenerated electrons and photogenerated holes, and the recombination probability therebetween is reduced. The larger interlayer spacing can provide a smoother path for the migration of carriers, improve the migration ability of carriers, and enhance the efficiency of photocatalytic reaction. Moreover, the doping process forms a new energy level and band gap, reduces the band gap width of the carbon nitride, and effectively improves the visible light utilization rate of the material. In addition, the ammonium chloride generates gas during the pyrolysis process, which effectively expands the pore structure and specific surface area of the material, and finally obtains the manganese-chlorine co-doped carbon nitride with a petal-shaped structure, which effectively increases the specific surface area of the material, provides more reaction active sites, and significantly improves the photocatalytic activity of the coating.
[0017] Furthermore, the mass ratio of ammonium chloride to melamine is (0.8-1.2):1, which can promote the formation of a more regular and uniform carbon nitride structure, thereby improving its specific surface area, pore structure and other properties.
[0018] Furthermore, the mass ratio of manganese chloride to melamine is (0.01-0.2):4, which can further adjust the band gap of carbon nitride, and low-energy photons are sufficient to trigger the photocatalytic reaction of the sample, which effectively improves the use of visible light.
[0019] Furthermore, the grinding time is 30 to 50 min, which can make the material particle size uniform, improve the reaction activity and enhance the structural stability.
[0020] Furthermore, during the grinding process, the mixture is ground to 400-600 meshes, which can effectively control the morphology and distribution of the particles and avoid the generation of oversized or undersized particles.
[0021] Furthermore, the heat treatment temperature is 500-600°C, the heating rate is 4-5°C / min, and the calcination time is 1.5-2.5 h, which can enable the carbon and nitrogen elements in the precursor to react effectively. High-temperature heat treatment can form more pores on the surface of carbon nitride, increase the specific surface area, and help enhance its adsorption and catalytic activity.
[0022] In addition, the present invention also discloses a photocatalytic hydrophobic synergistic self-cleaning coating, which contains a manganese-chlorine co-doped carbon nitride in the present invention. In addition, during the preparation of the coating, the epoxy resin is reacted with polydimethylsiloxane and 3-aminopropyltriethoxysilane to undergo a cross-linking reaction under the action of a catalyst, thereby achieving ring-opening polymerization of the epoxy resin and forming a three-dimensional network structure, which effectively improves the internal bonding force of the coating. In addition, the end groups of 3-aminopropyltriethoxysilane and polydimethylsiloxane react with the epoxy resin to graft the siloxane chains into the network structure, which effectively improves the hydrophobic properties of the coating. The manganese-chlorine co-doped carbon nitride added in addition has a nanoflower-like structure, which can effectively improve the roughness of the coating and enhance the super-hydrophobic properties of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0024] Figure 1 X-ray diffraction (XRD) patterns of the prepared photocatalysts of Example 1 and Comparative Example 1; Figure 2 Fourier transform infrared spectroscopy (FTIR) spectra of the prepared photocatalysts of Example 1 and Comparative Example 1; Figure 3 Scanning electron microscope (SEM) images of the photocatalysts prepared in Example 1 and Comparative Example 1, showing the surface morphology and microstructure of the materials; Figure 4 The nitrogen adsorption-desorption isotherms (BET surface areas) of the prepared photocatalysts of Example 1 and Comparative Example 1; Figure 5 This is the XPS graph of the photocatalyst prepared in Example 1; Figure 6 The UV-visible spectra (left) and band gap diagrams (right) of the prepared photocatalysts of Example 1 and Comparative Example 1; Figure 7 The photocatalytic degradation experimental effect diagram of Example 1 and Comparative Example 1; Figure 8 The FTIR spectra of the coatings prepared in Example 5, Comparative Example 2 and Comparative Example 3 before and after 24 accelerated aging tests (288 hours) are compared, showing the chemical changes of the materials during the aging process; Fig. 9The glossiness change diagram of the coatings prepared in Example 5, Comparative Example 2 and Comparative Example 3 before and after 24 accelerated aging tests (288 hours) reflects the durability and appearance stability of the coatings; Fig.10 The contact angle change diagrams of Example 5, Comparative Example 2 and Comparative Example 3 before and after 24 accelerated aging tests (288 hours) characterize the hydrophobicity and surface characteristics of the materials. DETAILED DESCRIPTION
[0025] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0026] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0027] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0028] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0029] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0030] The present invention provides a method for preparing manganese-chlorine co-doped carbon nitride, comprising the following steps: S1: uniformly grinding melamine, ammonium chloride and manganese chloride for 30-50 min until the particle size of the mixed powder is 400-600 meshes to obtain a mixed powder; The mass ratio of the ammonium chloride to melamine is (0.8-1.2):1, and the mass ratio of the manganese chloride to melamine is (0.01-0.2):4.
[0031] S2: heat treating the powder in an air atmosphere at a temperature of 500-600° C., a heating rate of 4-5° C. / min, and a calcination time of 1.5-2.5 h to obtain the manganese-chlorine co-doped carbon nitride.
[0032] At the same time, the present invention also discloses a photocatalytic hydrophobic synergistic self-cleaning coating prepared based on the above-mentioned manganese-chlorine co-doped carbon nitride. The preparation process of the coating is: after mixing epoxy resin, polydimethylsiloxane (PDMS), 3-aminopropyltriethoxysilane (APTES) and a catalyst, stirring at 70-80°C for 20-30 minutes, adding a curing agent to obtain a water-based epoxy resin emulsion; then adding the manganese-chlorine co-doped carbon nitride to obtain the photocatalytic hydrophobic synergistic self-cleaning coating.
[0033] The catalyst may be dibutyl diacid catalyst, the mass ratio of epoxy resin to PDMS and APTES is 9:1:0.2, the mass ratio of curing agent to epoxy resin is 1:3, and the mass ratio of manganese chlorine co-doped carbon nitride to epoxy resin is 1:150.
[0034] The photocatalytic hydrophobic synergistic self-cleaning coating of the present invention effectively combines hydrophobicity and photocatalytic activity. The graphite phase carbon nitride material exhibits good photocatalytic performance. Its stacked layered petal-like structure not only provides a larger pore structure and specific surface area, but also forms a new energy level and band gap, reduces the electron-hole recombination rate, thereby providing more reactive sites, and significantly improves the photocatalytic activity of the coating. At the same time, the surface roughness of the structure increases, thereby enhancing the hydrophobic properties of the material. In addition, the hydrophobicity and durability of the coating are further improved by modifying the low surface energy material.
[0035] The self-cleaning coating prepared by the present invention is a fluorine-free and solvent-free coating, which has both hydrophobic properties and photocatalytic activity, and can effectively remove inorganic pollutants in the actual environment and degrade organic pollutants. The coating exhibits excellent water resistance and anti-aging properties. The addition of stacked layered petal-like graphite phase carbon nitride materials significantly improves the aging resistance, water resistance and mechanical strength of the coating, mainly due to the strong interface effect between the nanoparticles and the matrix. The present invention achieves excellent performance of the coating in terms of pollutant degradation performance and anti-ultraviolet aging performance through a simple preparation strategy. It has the characteristics of green environmental protection, low raw material cost, simple preparation process and sustainability, and provides a new solution for achieving efficient and sustainable treatment of actual environmental pollutants in outdoor application scenarios and constructing multifunctional integrated coatings.
[0036] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0037] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0038] Example 1 A method for preparing manganese-chlorine co-doped carbon nitride comprises the following steps: 4 g of melamine (C3H6N6), 4 g of ammonium chloride (NH4Cl) and a certain amount (0.144 g) of manganese chloride (MnCl2·4H2O) were placed in an agate mortar and ground thoroughly for 30 min until they were mixed evenly to obtain a uniform mixed powder. According to the 0.15 wt% of Mn in melamine, it is 0.0144 g. Subsequently, the mixed powder was transferred to a covered crucible and heated to 550 °C in a muffle furnace for 2 h and kept warm for 2 h to finally obtain a photocatalyst (sample labeled MCCN).
[0039] Comparative Example 1 4 g of melamine was put into an agate mortar and ground thoroughly for 30 minutes until it was mixed evenly to obtain a mixed powder. Subsequently, the mixed powder was transferred to a covered crucible and heated to 550 °C in a muffle furnace for 2 h and kept at this temperature for 2 h to finally obtain a photocatalyst (sample marked as CN).
[0040] Figure 1The XRD diagrams of the photocatalysts prepared in Example 1 and Comparative Example 1 show the crystal structure characteristics of the materials. The analysis results show that pure carbon nitride CN (i.e., the sample in Comparative Example 1) has two obvious characteristic diffraction peaks at 13.5 ° (100) and 27.5 ° (002), which correspond to the interlayer stacking of the triazine ring structural unit and the conjugated aromatic system in the carbon nitride plane, respectively. These two independent characteristic peaks can also be observed in the sample prepared in Example 1, indicating that the crystal structure of carbon nitride has not changed significantly after the introduction of Mn and Cl, although the intensity of its (100) and (002) peaks has been significantly weakened. In addition, for the sample in Example 1, the peak position of the (002) plane moves slightly from 27.84 ° to 27.53 °, with a negative displacement, and the corresponding interlayer spacing increases from 0.320 nm to 0.323 nm. This change may be caused by the doping of Mn and Cl atoms with larger atomic radius in the CN lattice, which leads to the increase of the interlayer spacing of CN due to the modification of Mn and Cl. The increase in interlayer spacing helps the separation of carriers, provides more space for photogenerated electrons and photogenerated holes, and reduces the probability of recombination between them. It improves the mobility of carriers. The larger interlayer spacing can provide a smoother path for the migration of carriers and enhance the efficiency of photocatalytic reactions.
[0041] Figure 2 The Fourier transform infrared spectra (FTIR) of the photocatalysts prepared in Example 1 and Comparative Example 1 reveal the chemical composition and functional group characteristics of the materials. As can be seen from the figure, at 808 cm -1 and 880 cm -1 The vibration peaks at 1200-1700 cm -1 The prominent peaks in the range of 3000-3500 cm -1 The broad peaks in the region are attributed to the stretching vibrations of primary and secondary amines. All samples show similar characteristics and vibration modes to CN, indicating that the doping of Mn and Cl elements does not destroy the structure of the tri-s-triazine group of CN, which is consistent with the results of XRD.
[0042] Figure 3 The scanning electron microscope (SEM) images of the photocatalysts prepared in Example 1 and Comparative Example 1 show the surface morphology and microstructure of the materials. It can be seen from the figure that the SEM image of the original CN shows an almost flat lamellar structure of the original CN, while Example 1 presents a relatively uniform, dense and irregular stacked layered petal-like structure composed of nanoflakes and nanorods due to the doping of Mn and Cl.
[0043] Figure 4The nitrogen adsorption-desorption isotherms (BET surface area) of the photocatalysts prepared in Example 1 and Comparative Example 1 show that the introduction of Mn and Cl into the CN matrix leads to a significant increase in the specific surface area. Specifically, the specific surface area of 3Mn-ClCN is 19.6185 m 2 ·g -1 , significantly exceeding CN's 5.1624 m 2 ·g -1 , an increase of 3.8 times.
[0044] Figure 5 The XPS study results of the photocatalyst prepared in Example 1 confirmed that Mn and Cl were successfully doped into the carbon nitride matrix.
[0045] Figure 6 The UV-visible spectra and band gap diagrams of the photocatalysts prepared in Example 1 and Comparative Example 1 show that the light absorption capacity of MCCN is enhanced compared with CN. Since Mn has strong light absorption characteristics, the introduction of Mn leads to an expansion of the visible light absorption range of CN. The band gap values (E g ) are 2.53 and 2.35 eV. The synergistic effect of Mn and Cl co-doping significantly narrows the band gap of MCCN compared to CN, indicating that low-energy photons are now sufficient to trigger the photocatalytic reaction of the sample, effectively improving the use of visible light.
[0046] In order to verify the photocatalytic performance of the material prepared in the present invention, the degradation performance of the photocatalytic materials prepared in Example 1 and Comparative Example 1 on RhB was tested. The specific test process is as follows: The photocatalytic activity of the catalyst and the composite material was evaluated by testing the removal rate of 10 mg / L RhB solution. A 300W xenon lamp was used to simulate sunlight irradiation. 100 mL RhB solution and 50 mg photocatalyst (the corresponding catalyst dosage was 0.5 g·L) were added to the beaker. −1 ). A rotor was added and the catalyst was evenly dispersed in the solution system by magnetic stirring. Before photocatalysis, the beaker was placed in a closed dark box for 30 minutes to achieve adsorption / desorption equilibrium. Photocatalytic degradation was then performed for another 90 minutes. The RhB solution in the beaker was taken out every 10 minutes, and the absorbance of RhB was measured at 554 nm using a UV-visible spectrophotometer. Figure 7 The photocatalytic degradation experimental effect diagram of RhB prepared in Example 1 and Comparative Example 1 shows that after 60 minutes of photoreaction, the removal rates of RhB by the photocatalysts prepared in Comparative Example 1 and Example 1 are 47% and 99%, respectively. The manganese-chlorine co-doped carbon nitride prepared in the present invention has good photocatalytic pollutant degradation performance.
[0047] Example 2 A method for preparing manganese-chlorine co-doped carbon nitride comprises the following steps: S1: uniformly grinding melamine, ammonium chloride and manganese chloride for 30 min until the particle size of the mixed powder is 400 mesh to obtain a mixed powder; The mass ratio of the ammonium chloride to melamine is 0.8:1, and the mass ratio of the manganese chloride to melamine is 0.01:4.
[0048] S2: heat treating the powder in an air atmosphere at a temperature of 500° C., a heating rate of 5° C. / min, and a calcination time of 2.5 h to obtain the manganese-chlorine co-doped carbon nitride.
[0049] Example 3 A method for preparing manganese-chlorine co-doped carbon nitride comprises the following steps: S1: uniformly grinding melamine, ammonium chloride and manganese chloride for 50 min until the particle size of the mixed powder is 400 mesh to obtain a mixed powder; The mass ratio of the ammonium chloride to melamine is 1.2:1, and the mass ratio of the manganese chloride to melamine is 0.2:4.
[0050] S2: heat treating the powder in an air atmosphere at a temperature of 600° C., a heating rate of 5° C. / min, and a calcination time of 1.5 h to obtain the manganese-chlorine co-doped carbon nitride.
[0051] Example 4 A method for preparing manganese-chlorine co-doped carbon nitride comprises the following steps: S1: uniformly grinding melamine, ammonium chloride and manganese chloride for 40 min until the particle size of the mixed powder is 500 mesh to obtain a mixed powder; The mass ratio of the ammonium chloride to melamine is 1:1, and the mass ratio of the manganese chloride to melamine is 0.1:4.
[0052] S2: heat treating the powder in an air atmosphere at a temperature of 550° C., a heating rate of 4.5° C. / min, and a calcination time of 2 h to obtain the manganese-chlorine co-doped carbon nitride.
[0053] Example 5 A method for preparing a photocatalytic hydrophobic synergistic self-cleaning coating comprises the following steps: 30 g of epoxy resin, a certain amount of polydimethylsiloxane (the mass ratio of PDMS to epoxy resin was 1:9), 3-aminopropyltriethoxysilane (the mass ratio of APTES to PDMS was 1:5) and dibutyl diacid catalyst were stirred at 70°C for 20 min, and then 10 g of curing agent was added and continued to stir to prepare a waterborne epoxy resin emulsion (WEP emulsion). 200 mg of the prepared manganese-chlorine co-doped carbon nitride (MCCN) was slowly added to the mixture and stirred evenly to prepare a manganese-chlorine co-doped carbon nitride modified waterborne epoxy resin emulsion (MCCN / WEP emulsion).
[0054] Furthermore, 25 g of the MCCN / WEP emulsion was coated on a polytetrafluoroethylene template (10 cm×10 cm) and dried under ambient conditions for one week to obtain a photocatalytic hydrophobic synergistic self-cleaning coating. The thickness of the obtained dry film was about 0.5 mm.
[0055] MCCN was anchored on the coating surface by a step-by-step coating method. Specifically, the mixture without catalyst (i.e., pure WEP emulsion) was first coated on the surface of the glass slide with a rod-shaped applicator. When the coating surface was semi-dry, the catalyst dispersion (MCCN / WEP emulsion) was coated for the second time in the same way to form a uniform film. The film was cured at room temperature for 48 h. The prepared sample was labeled as Epoxy-PDMS-MCCN.
[0056] Comparative Example 2 30 g of epoxy resin, a certain amount of PDMS (9:1 mass ratio with epoxy resin), APTES (stoichiometric relative to the OH groups of PDMS) and dibutyl diacid catalyst were stirred at 80 °C for 20 min, followed by the addition of 10 g of curing agent and continued stirring. 25 g of the obtained emulsion was poured onto a polytetrafluoroethylene template (10 cm × 10 cm) and dried under ambient conditions for 7 days. The thickness of the dried film was about 0.5 mm, and the prepared sample was labeled as Epoxy-PDMS.
[0057] Comparative Example 3 30 g of epoxy resin and 10 g of curing agent were stirred continuously. 25 g of the obtained emulsion was poured onto a polytetrafluoroethylene template (10 cm×10 cm) and dried under ambient conditions for one week. The thickness of the dry film was about 0.5 mm, and the prepared sample was labeled as Epoxy.
[0058] In order to test the performance of the coating prepared above, an accelerated aging test was conducted. The specific test process is as follows: using an accelerated aging tester for weathering exposure within 288 h. Specifically, at a UV intensity of 0.89 W / m 2The accelerated aging test was carried out under ultraviolet light (340 nm), the test temperature was 60℃, and the exposure cycle was 12 hours, divided into 8 hours of ultraviolet exposure and 4 hours of condensation. The aging resistance was studied using FTIR, gloss and water contact angle test (WCA) analysis. According to GB / T 9574-2007, the 60° gloss of different coatings before and after weathering analysis was measured using a gloss meter. Three different positions of the coating were tested, and the average gloss value was used to evaluate the anti-aging performance of the coating under ultraviolet irradiation.
[0059] Figure 8 The FTIR images of the coatings prepared in Example 5, Comparative Example 2 and Comparative Example 3 before and after 24 accelerated aging tests (288 hours) are shown in the figure. It can be seen from the figure that after 24 accelerated aging tests (288 hours), the coatings still have the characteristic peaks of the main functional groups, which are located at 1735 cm -1 The peak at is due to the carbonyl stretching produced by the oxidation of CH groups in the coating matrix, indicating that the structure of the coating is stable.
[0060] Fig. 9 The gloss change diagram of the coatings prepared in Example 5, Comparative Example 2 and Comparative Example 3 before and after 24 accelerated aging tests (288 hours) is shown. It can be seen from the figure that the coating with added nanoparticles shows less gloss loss during the accelerated weathering process. It can be inferred that the addition of nanoparticles can alleviate the effective degradation of the coating and improve the gloss retention of the epoxy resin coating.
[0061] Fig.10 The water contact angle change diagram of the coating prepared in Example 5 before and after 24 accelerated aging tests (288 hours) is shown. The water contact angles of all coatings decrease after aging. After the aging test, the WCA value of the pure epoxy coating decreases significantly, while the WCA values of other coatings decrease less. The composite coating prepared in the present invention has a water contact angle of 125.9° before the aging test and a water contact angle of 105.6° after the aging test, and has stable hydrophobic properties.
[0062] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
[0063] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing manganese and chlorine co-doped carbon nitride, characterized in that: The following steps are involved: S1: uniformly grinding melamine, ammonium chloride and manganese chloride to obtain a mixed powder; S2: heat-treating the powder in an air atmosphere to obtain the manganese-chlorine co-doped carbon nitride.
2. The method for preparing manganese-chlorine co-doped carbon nitride according to claim 1, characterized in that: The mass ratio of ammonium chloride to melamine is (0.8-1.2):
1.
3. The method for preparing manganese-chlorine co-doped carbon nitride according to claim 1, characterized in that: The mass ratio of the manganese chloride to melamine is (0.01-0.2):
4.
4. The method for preparing manganese-chlorine co-doped carbon nitride according to claim 1, characterized in that: The grinding time is 30 to 50 min.
5. The method for preparing manganese-chlorine co-doped carbon nitride according to claim 1, characterized in that: During the grinding process, the mixture is ground to 400-600 meshes.
6. The method for preparing manganese-chlorine co-doped carbon nitride according to claim 1, characterized in that: The heat treatment temperature is 500-600° C., the heating rate is 4-5° C. / min, and the calcination time is 1.5-2.5 h.
7. A manganese-chlorine co-doped carbon nitride, characterized in that: Prepared by the method according to any one of claims 1 to 6.
8. A photocatalytic hydrophobic synergistic self-cleaning coating, characterized in that: The invention comprises a manganese-chlorine co-doped carbon nitride as claimed in claim 7.
9. The method for preparing a photocatalytic hydrophobic synergistic self-cleaning coating as claimed in claim 8, characterized in that: After epoxy resin, polydimethylsiloxane, 3-aminopropyltriethoxysilane and a catalyst are mixed, stirred for reaction, and then a curing agent is added to obtain a water-based epoxy resin emulsion; then the manganese-chlorine co-doped carbon nitride is added to obtain the photocatalytic hydrophobic synergistic self-cleaning coating.
10. A photocatalytic hydrophobic synergistic self-cleaning coating, characterized in that: It comprises a bottom layer and a surface layer, wherein the bottom layer is obtained by drying a water-based epoxy resin emulsion, and the surface layer is obtained by drying a photocatalytic hydrophobic synergistic self-cleaning coating as claimed in claim 8.